A menekültek és bevándorlók Európában az 1950-es évektől napjainkig - Cseresnyés Ferenc (Közép-európai közlemények, 2020)
The Geneva Convention Relating to the Status of Refugees was adopted during the Cold War era (1951) based on the operational experience of Eastern European dictatorships. As a consequence, it was relatively easy to draw up forms of persecution for which an applicant was granted refugee status. Refugees were accepted and integrated eventually. However, the relatively simple distinction between refugees and migrants has changed since the regime changes in Eastern Europe. The attitude of host states in the Western world has changed: they began to interpret the Convention restrictively. It was not problematic, as the lacking procedural rules of the Convention made this possible, as did the completely transformed international political environment. (Eastern European dictatorships have come to an end; formally the whole of Europe has become a democracy: thus discrediting political persecution). Concerned about their labor markets as well, the destination countries welcomed only a few “real” refugees, not those whose motivation for migration were questionable. (Obviously, this approach was supported by the security expectations of their population.) This concern and distancing changed completely after 25 years. In the course of the mass migration in 2015, worries of the host states’ population became immaterial, humanitarian and global aspects took precedence over the aspects of the formally applicable Convention, while national/state interests were sidelined.